10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Modern healthcare system produces large amount of sensitive clinical data, but no existing framework simultaneously addresses and satisfy rigorous security guarantees, storage efficiency and the throughput demand of clinical operations/transactions. All existing framework addresses these requirements in isolation such as cloud architectures lack cryptographic immutability and standalone blockchain systems suffer by high gas costs and block size limitations. To resolve this gap, we present the Blockchain-Integrated Cloud Compression Model (BICCM) a three-tier architecture that combines (i) Ethereum based smart contracts with Role-Based Access Control (RBAC) and Zero-Knowledge Proof (ZKP) authentication, (ii) Lempel-Ziv-Welch (LZW) lossless compression applied at a dedicated light node layer and (iii) a blockchain secured cloud object store with on-chain SHA-256 has anchoring. COVID-19 medical records from Pakistan Bureau of statistics (PBS-2023) in six size classes range from 4.93 to 39.80KB were used for evaluation.BICCM achieves 65.81 to 85.34% storage reduction, 64.3 to 84.4% gas savings (mean 76.4%), 45.4 to 83.2% execution-time improvement, and 50% transaction cost reduction Compared to the traditional Ethereum blockchain outperformed four competing algorithms (LZ-String, LZ77, Run-Length Encoding, Huffman) for all evaluated data sizes, attaining compression ratios of 2.92 to 6.82. Smart contract deployment on auxiliary nodes reduced ETH costs by 88.6% compared to the main deployment node. BICCM offers a scalable, safe and HIPAA/GDPR complaint platform for blockchain cloud healthcare data management with full implementation across all twelve assessed security criteria. Future work will follow a strategy for federated learning integration and post-quantum cryptography transition.